Giving Types of Organic Materials on The Effect of Physical Properties of Ultisol Soil, South Rantau Sub-District - Fitra Syawal Harahap; Ida Rumia Manurung; Iman Arman; Nurliana Harahap; Fauzi Ahmad Syawaluddin; Rendi Fitra Yana (Universitas Sebelas Maret, 2023)
This study entitled the provision of various organic materials on physical properties and ultisols in South Rantau District Labuhan Batu Regency was carried out in the experimental garden at the Labuhan Batu University, North Sumatra. This study aims to determine the best type of organic material to improve the physical properties of ultisol soil from the South Rantau land at the Labuhan Batu. This study used a non-factorial randomized block design (RBD) with a treatment factor of 8 types of organic matter and 3 replications so that there were 27 experimental units. L0 Treatment: Control, L1: Palm oil solid waste, L2: Sugar factory waste, L3: Fish waste, L4: animal feed waste, L5: Chicken manure, L6: Cow manure, L7: Leguminose compost, L8: Compost organic waste fertilizer Medan city with a dose of each organic material 150g / 10 kg TKO. After incubation, bulk density (g /cm3) was taken using the Ring Sample method, Total Pore Space (%) with soil particle density and permeability (cm/hour) using the De Bootd method. Research results fish waste has the highest significant effect in improving soil physical properties, such as reducing soil bulk density, namely 1.02 g / cm3, and increasing the total soil pore space by 61.63%. In contrast, the highest soil permeability is obtained in the treatment of animal feed waste, which is 59.51 cm/hour while the lowest was in the control treatment of 28.18 cm/hour. The application of fish waste had the highest significant effect in improving the physical properties of the soil, such as reducing the bulk density of the soil.